The Implementation of Canva as a Media for Learning English at SMK Negeri 2 Singaraja - sugiani nyoman (Universitas Nurul Jadid, 2023)
This study intends to determine teachers’ challenges in teaching English using technological media, namely the Canva application. in this study, researchers used qualitative descriptive methods. An SMK N 2 Singaraja teacher participated in this study because he implemented the Canva application as a learning medium to meet the current educational system. According to (Titiyanti et al., 2022), With the help of Canva, teachers may provide a one-of-a-kind opportunity for students to engage their abilities and motivation in learned material. To get the data, the researcher used the semi-structured interview method as a data instrument for data collecting. The results of this study state that Canva media is very suitable for learning English because it can improve students’ ability to write, creativity, critical thinking, and motivation to learn. However, the teacher cannot trace this application, so the teacher cannot see the students’ work process in making brochures.